AN INVESTIGATION OF THE SIMILARITIES AND DIFFERENCES BETWEEN ENGLISH LITERATURE AND ENGLISH LANGUAGE TEACHING MASTER’S THESES IN TERMS OF SWALES’ CARS MODEL - Uymaz, Eren (PEOPLE: International Journal of Social Sciences, 2017)
This study aims at identifying the differences and similarities between English literature master’s theses and English language teaching master’s theses in terms of John Swales’ Creating a Research Space (CARS) model. John Swales originated this model for the introduction parts of the research articles and offered researchers a guideline to follow while writing the introduction parts of research articles. This research tries to fill a gap by adapting this model to examine the introduction parts of the English literature and English language teaching master’s theses. For this end, the researcher chose 5 English language and literature (ELIT) MA (Master of Arts) theses and 5 English language teaching (ELT) MA (Master of Arts) theses all written in 2014 by Turkish students. The results indicated that there are differences between these two theses types in terms of Establishing a Territory (Move 1), Establishing a Niche (Move 2) and Occupying a Niche (Move 3) moves. Based on the findings, it is recommended that English literature master’s theses and English language teaching master’s theses be evaluated in a different perspective although literature and language teaching are related with each other.